Exploring the relationship between the physical literacy and physical activity level of Filipino adults through a mixed-method approach - Togueño, Resh Vnzi S. 2000-; Cabading, Dan Angelo F. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2025)
Physical Literacy-based policies have been used to amend the increasing prevalence of physical inactivity in the world. The goal of this study is to explore the relationship between physical literacy (PL) and physical activity (PA) levels of millennial Filipinos from Brgy. Pansol, Quezon City, by adopting a mixed-method approach. This study will give an insight into the current physical literacy and activity levels of Filipino adults which can help build a foundation for future policies. The PPLQ was used to measure physical literacy scores and the IPAQ-SF to measure physical activity levels. Semi-structured interviews were used to explore the development of the PL and PA level of certain participants. The PPCT-model and Braun and Clarke’s thematic analysis were used to analyze the qualitative data. Significant positive correlations were found between PL, its domains, and PA levels, extending the findings from previous studies. The thematic analysis highlighted the importance of several factors that affect the development of PL and PA engagement, namely, social interactions, availability of space for PA engagement, and the lack of formal education as a source of knowledge regarding PL and PA.
Thesis (Bachelor of Sports Science)-University of the Philippines Diliman
Includes bibliographies
Keywords: Exercise; Adulthood